2005
DOI: 10.3168/jds.s0022-0302(05)72938-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profile of Total Body Energy Content of Holstein Cows in the First Three Lactations

Abstract: Weekly total body energy content (TBEC) was calculated for 444 Holstein cows in their first 3 lactations. These calculations were based on body lipid and protein changes predicted from weekly changes in body condition score and live weight of each cow. In first lactation, cows lost TBEC during the initial 8 wk, regained it by wk 22, and continued to build up their reserves until wk 37. Cows started lactations 2 and 3 with considerable reserves from the dry period that they used during the first 13 wk of lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 15 publications
3
25
0
1
Order By: Relevance
“…In dairy cattle, physiological adaptations to lipid metabolism, and associated changes in gene expression, have been shown to favour lipid accretion in gestation and mobilisation in early lactation (Blanc et al, 2006). Given this, it is not surprising that the temporal pattern of change in body reserves throughout the reproductive cycles can be modulated by genetic selection (Banos et al, 2005). These genetically driven changes in Figure 6 Example of individual animal trajectories before, during and after an environmental perturbation for (a) milk yield and (b) plasma glucose in 16 dairy goats.…”
Section: Friggens Blanc Berry and Puilletmentioning
confidence: 99%
See 1 more Smart Citation
“…In dairy cattle, physiological adaptations to lipid metabolism, and associated changes in gene expression, have been shown to favour lipid accretion in gestation and mobilisation in early lactation (Blanc et al, 2006). Given this, it is not surprising that the temporal pattern of change in body reserves throughout the reproductive cycles can be modulated by genetic selection (Banos et al, 2005). These genetically driven changes in Figure 6 Example of individual animal trajectories before, during and after an environmental perturbation for (a) milk yield and (b) plasma glucose in 16 dairy goats.…”
Section: Friggens Blanc Berry and Puilletmentioning
confidence: 99%
“…The first derivative of such profiles can be used as a measure of rate of change in the trait. Such models, commonly termed test-day models, have been fitted to longitudinal data for many performance traits including milk production, body condition score and growth rate (Berry et al, 2003;Banos et al, 2005). They offer a means to concisely describe key elements of robustness.…”
Section: Managing Robustness: Measuring and Predictingmentioning
confidence: 99%
“…In early lactation, increase in feed intake is not sufficient to meet energy requirements of milk production in dairy cattle (Block et al, 2001;Banos et al, 2005;Chebel et al, 2008). Cows therefore enter a negative energy state (Block et al, 2001) in which they mobilize tissue reserves to meet increased energy requirements (Friggens et al, 2004).…”
Section: Short Communicationmentioning
confidence: 99%
“…Body condition score (BCS) assesses the energy reserves of dairy cows and is therefore commonly used as an indicator of the extent and the duration of the negative energy balance (Roche et al, 2009) in early lactation, period in which the feed intake is not sufficient to meet energy requirements of milk production (Banos et al, 2005;Chebel et al, 2008). Many studies reported a moderate heritability of BCS (from 0.25 to 0.35) in dairy breeds (Berry et al, 2002;Pryce and Harris, 2006;Dal Zotto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%